Type species designation for Archaebranchinecta Rogers & Coronel (Branchiopoda: Anostraca) - Rogers, D. Christopher (Zootaxa, 2019)
Over the course of my career I have described nine Branchiopod genera and one subgenus, either alone or with other researchers. From these, four genera and the subgenus belong to Anostraca. But I was remiss in designating type species for one of those taxa which caused the name to become unavailable. This short communication is to rectify this unfortunate error on my part.